Performance evaluation of PC routers using a single server multi-queue system with a reflection technique. - Jirachiefpattana, A.
In this paper, a cyclic service system with switch over times introduced by K.S. Watson is used to define the characteristics of the queueing model of a PC router developed at La Trobe University, and based on Vance Morrison's PC router. Two methods of approximating its performance are investigated. The first one is to modify the mean waiting-time approximations for a single server multi-queue system with nonexhaustive cyclic service, and with non-zero switch over times of the server between consecutive queues introduced by O.J. Boxma and B. Meister, while the second is to develop a tool based on a reflection technique. The second method is chosen to measure the delay for three packet sizes (64,576 and 1514 bytes) with four types of PC router (our PC router with and without IP checksum verificiation and Vance Morrison's PC router-packet driver and non-packet driver versions). The results of performance analysis are presented.
Keywords: PC routers; IP routers; Performance evaluation; Queueing model; Reflection technique